Method of Understanding Hadith in the Book Adab Al-'Alim Wa Al-Muta'alim KH. M. Hasyim Asy'ari - Samsudin, Samsudin; Tajul Arifin (al-Afkar, Journal For Islamic Studies, 2025)
The book Adab Al-'Alim wa Al-Muta'allim by KH. M. Hasyim Asy'ari is one of the important works in the tradition of Islamic education, especially in the context of Islamic boarding schools in Indonesia. This book discusses the ethics and manners of an alim (scholar) and student in the teaching and learning process. One of the important aspects in this book is the method of understanding the hadith presented by KH. Hasyim Asy'ari. Hasyim Asy'ari emphasized the importance of a comprehensive approach in understanding hadith, which includes several main methods, namely the Ijtihad approach, the muqaranah approach between verses and hadiths, the bayan approach through the atsar of companions, the qaul of salafus salih scholars, and verses to help understand the meaning. Through this book, KH. Hasyim Ash'ari shows that understanding hadith requires not only mastery of linguistics, but also extensive knowledge of the social context, and principles of Islamic law. This book is an important reference in teaching hadith in Islamic boarding schools and other Islamic religious institutions in Indonesia.